HER2-low inflammatory breast cancer: Clinicopathologic features and prognostic implications. (October 2022) - Tarantino, Paolo; Niman, Samuel M.; Erick, Timothy K.; Priedigkeit, Nolan; Harrison, Beth T.; Giordano, Antonio; Nakhlis, Faina; Bellon, Jennifer R.; Parker, Tonia; Strauss, Sarah; Jin, Qingchun; King, Tari A.; et al.
Abstract: Background: HER2)-low expression is a predictive biomarker for novel anti-HER2 antibody-drug conjugates. However, little is known about its clinical significance in inflammatory breast cancer (IBC). Methods: Patients diagnosed with HER2-negative IBC between December 1999 and December 2020 were identified from the Dana-Farber Cancer Institute IBC registry. Patients were divided into HER2-low (IHC 1+ or 2+/ISH–) and HER2-zero (IHC 0), comparing clinicopathologic features and disease outcomes between the two subgroups. Results: The study included 276 patients. Among patients with stage III (n = 209) and stage IV (n = 67) IBC, 54% and 39% had HER2-low tumours, respectively. Oestrogen receptor (ER)-expressing tumours were more common in patients with HER2-low versus HER2-zero stage III IBC (65% versus 38%, p < 0.01). Among stage III patients undergoing surgery (n = 182), pathologic complete response (pCR) rates were higher for HER2-zero versus HER2-low IBC (11% versus 6%, OR: 1.8, 95%CI:0.6–5.3), but minimal differences persisted when separately analysing pCR by ER status. Similar invasive disease-free survival (iDFS) outcomes were observed among ER-positive HER2-zero versus HER2-low IBC (48-month iDFS: 63% versus 63%, HR: 1.10, 95%CI:0.57–2.13) and ER-negative HER2-zero versus HER2-low IBC (48-month iDFS: 28% versus 25%, HR: 1.19, 95%CI:0.69–2.04). Differences in overall survival (OS) were small, both among ER-positive HER2-zero versus HER2-low IBC (48-month OS: 80% versus 81%, HR: 0.82, 95%CI:0.39–1.73) and ER-negative HER2-zero versus HER2-low IBC (48-month OS: 34% versus 47%, HR: 1.34, 95%CI: 0.74–2.41). Conclusions: Marginal differences in clinicopathologic features and outcomes were observed in HER2-low versus HER2-zero IBC when controlling for ER status, not supporting the definition of HER2-low as a distinct subtype of IBC. Highlights: Trastuzumab deruxtecan showed to prolong survival in HER2-low breast cancer (BC). No data exist on the clinical role of HER2-low expression in inflammatory BC (IBC). We found more ER-expressing tumours among stage III HER2-low (versus HER2-zero) IBC. As in non-IBC, no clear prognostic role emerged for HER2-low expression in IBC. Our results do not support HER2-low as a distinct subtype of IBC.